Extracellular vesicles from human saliva promote hemostasis by delivering coagulant tissue factor to activated platelets - Yu, Y.; Altevogt, Peter (Journal of thrombosis and haemostasis, 2018)
Essentials Human salivary extracellular vesicles (EVs) expose coagulant tissue factor (TF). Salivary EVs expose CD24, a ligand of P-selectin. CD24 and coagulant TF co-localize on salivary EVs. TF+/CD24+ salivary EVs bind to activated platelets and trigger coagulation. Summary Background Extracellular vesicles (EVs) from human saliva expose coagulant tissue factor (TF). Whether such TF-exposing EVs contribute to hemostasis, however, is unknown. Recently, in a mice model, tumor cell-derived EVs were shown to deliver coagulant TF to activated platelets at a site of vascular injury via interaction between P-selectin glycoprotein ligand-1 (PSGL-1) and P-selectin. Objectives We hypothesized that salivary EVs may deliver coagulant TF to activated platelets via interaction with P-selectin. Methods We investigated the presence of two ligands of P-selectin on salivary EVs, PSGL-1 and CD24. Results Salivary EVs expose CD24 but PSGL-1 was not detected. Immune depletion of CD24-exposing EVs completely abolished the TF-dependent coagulant activity of cell-free saliva, showing that coagulant TF and CD24 co-localize on salivary EVs. In a whole blood perfusion model, salivary EVs accumulated at the surface of activated platelets and promoted fibrin generation, which was abolished by an inhibitory antibody against human CD24. Conclusions A subset of EVs in human saliva expose coagulant TF and CD24, a ligand of P-selectin, suggesting that such EVs may facilitate hemostasis at a site of skin injury where the wound is licked in a reflex action.
Gesehen am 19.10.2020